The Efforts of Islamic Religious Education Teachers in Shaping Students’ Religious Character - ZA, M. Yarham (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
This study discussed the efforts of Islamic Religious Education teachers to shape students’ religious character at SDN Inpres Silae. Using a qualitative approach, data were collected through observation, interviews, and documentation, and analyzed through data reduction, presentation, and verification. Findings revealed that teachers foster students’ religious character through role modeling and habituation, supported by activities such as congregational and Duha prayers, daily Quran recitation, dzikir, weekly almsgiving, monthly Islamic parenting sessions, and annual events, including short-term Islamic boarding programs, communal iftar, and Prophet Muhammad’s birthday celebrations. This study emphasized that teachers’ efforts, combined with school-based religious activities, play a vital role in strengthening students’ religious values and require support from the wider community.